Beyond folate antagonism: the unique pharmacological blueprint of methotrexate - Menon, Abhilash; Murugesan, Pradhiksha; Tamilarasan, Pillai Pooja; Palanisamy, Sai Ahil; Parthasarathy, Arun Kanniyappan (International Journal of Basic & Clinical Pharmacology, 2025)
Methotrexate (MTX) possesses a uniquely complex pharmacological profile characterized by nonlinear pharmacokinetics, saturable absorption, transporter-dependent distribution, and intracellular polyglutamation, all of which contribute to substantial interindividual variability in therapeutic response and toxicity. This review summarizes current evidence on MTX absorption kinetics, dose-dependent oral bioavailability, and the role of renal and hepatic pathways in systemic clearance. Special emphasis is placed on the formation and accumulation of MTX polyglutamates (MTX-PGs), which act as long-acting intracellular metabolites that enhance therapeutic duration but may also increase the risk of adverse effects when present at higher concentrations. Genetic polymorphisms in key enzymes and transporters, including RFC1, FPGS, GGH, and members of the SLCO and ABC transporter families, significantly influence MTX disposition, efficacy, and toxicity, underscoring the expanding role of pharmacogenomics in individualized therapy. The review also highlights the relevance of routine laboratory monitoring, emerging biomarkers, and clinical dosing strategies, including split dosing and subcutaneous administration to optimize outcomes across oncology and autoimmune settings. By integrating current pharmacokinetic, pharmacodynamic, and pharmacogenomic insights, this work provides a comprehensive understanding of MTX’s therapeutic behaviour and supports the need for personalized approaches to maximize efficacy while minimizing adverse effects.